Improving Accessing Efficiency of Cloud Storage Using DeDuplication and Feedback Schemes (International Journal of Engineering and Computer Science, 2017)
File storage in cloud storage is handled by third parties. Files can be integrated, so that the users are able to access the files using the centralized management. Due to the great number of users and devices in the cloud network, the managers cannot effectively manage the efficiency of storage node. Therefore, hardware is wasted and the complexity for managing the files also increases. In order to reduce workloads due to duplicate files, we propose the index name servers (INS). It helps to reduce file storage, data de-duplication, optimized node selection, and server load balancing, file compression, chunk matching, real-time feedback control, IP information, and busy level index monitoring. Performance is also increased. By using INS the files can also be reasonably distributed and workload can be decreased